1989
DOI: 10.1063/1.344419
|View full text |Cite
|
Sign up to set email alerts
|

Radiation effects on ferroelectric thin-film memories: Retention failure mechanisms

Abstract: Ferroelectric thin-film (200–350 nm) memories were fabricated and tested. Two materials were used as memory cells: potassium nitrate (KNO3) and lead zirconate titanate (PbZr0.54Ti0.46O3, usually abbreviated as PZT). These devices were tested as arrays deposited either by thermal evaporation (in the case of KNO3) or sputtered films (PZT). Fully packaged devices were tested to determine switching speed and polarization (switched charge) as functions of temperature and applied voltage. Radiation hardness was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(66 citation statements)
references
References 37 publications
2
62
1
1
Order By: Relevance
“…The technique used in the DWM is known as positive-up-negative-down (PUND) measurement [10,11]. Figure 2 explains the DWM in brief.…”
Section: Methodsmentioning
confidence: 99%
“…The technique used in the DWM is known as positive-up-negative-down (PUND) measurement [10,11]. Figure 2 explains the DWM in brief.…”
Section: Methodsmentioning
confidence: 99%
“…In order to compensate leakage contribution, the so-called positiveup-negative-down (PUND) method has been employed 15 . Specimens for TEM studies were prepared by mechanical polishing, followed by Ar ion-milling.…”
Section: Iiexperimentalmentioning
confidence: 99%
“…Radiation effects are most easily observed in the hysteresis curve (i.e., the D-E curve) for ferroelectric (piezoelectric) materials. Scott et al (1989) observed that PZT films showed more symmetric hysteresis curves after 5 Mrad(Si) regardless of their conditions during irradiation. Schwank et al (1990) observed different D-E curve distortions when different bias conditions were applied during irradiation.…”
Section: Radiation Damage In Piezoelectric Transducersmentioning
confidence: 81%